2019
DOI: 10.1177/1744629519843012
|View full text |Cite
|
Sign up to set email alerts
|

‘I don’t feel like I’m in this on my own’: Peer support for mothers of children with intellectual disability and challenging behaviour

Abstract: This article reports on the peer support experiences of mothers with a son or daughter with intellectual disability and challenging behaviour. Engagement in parent peer support programs can improve family quality of life and may have multifaceted benefits at the interpersonal, intra-individual self-change and sociopolitical levels. Thirteen mothers were interviewed about their experiences of participating in a parent peer support program. Thematic analysis focused on the process elements of the program that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…Social support has been described as one of the most important protective factors for maintaining the health and well-being of parents of children with ID: It has been found that those who received formal or informal support were less stressed, more optimistic, and manifested increased levels of well-being and satisfaction with life [56,77,[89][90][91][92]. Thus, support programs or social networks for parents and their child with ID can improve family quality of life and help achieve multiple benefits both at the interpersonal and intraindividual levels [93,94]. In this sense, Bray, Carter, Sanders, Blake, and Keegan [95], found that the use of peer support programs by parents with children with ID, reduced the levels of psychological distress these parents suffered and strengthened their ability to cope with bringing up the child.…”
Section: Discussionmentioning
confidence: 99%
“…Social support has been described as one of the most important protective factors for maintaining the health and well-being of parents of children with ID: It has been found that those who received formal or informal support were less stressed, more optimistic, and manifested increased levels of well-being and satisfaction with life [56,77,[89][90][91][92]. Thus, support programs or social networks for parents and their child with ID can improve family quality of life and help achieve multiple benefits both at the interpersonal and intraindividual levels [93,94]. In this sense, Bray, Carter, Sanders, Blake, and Keegan [95], found that the use of peer support programs by parents with children with ID, reduced the levels of psychological distress these parents suffered and strengthened their ability to cope with bringing up the child.…”
Section: Discussionmentioning
confidence: 99%
“…Participants felt able to speak openly and discuss intimate areas of concern. These experiences resonated with reports from families who have accessed other specialist programmes and systems of peer-support (e.g., Borek et al, 2018;Dew et al, 2019;Dodds & Singer, 2017;Gore & Umizawa, 2011;Shilling et al, 2013) and were referenced in relation to engagement, learning and emotional support throughout sessions.…”
Section: E-pats Programme Principles Mechanisms and Processes Asmentioning
confidence: 67%
“…Findings suggest that the quality of the participant‐PL relationship is the main driver of intervention satisfaction and depends largely on how well matched the participant and PL are. The importance of a favourable match and the process in which matches are formed has also been highlighted in other peer support interventions targeting T2D and other health conditions 15,24–27 . In these studies, researchers paired individuals based on similarities in sex, 24 age, 24–26,28 sociocultural background, 27 geographic residence, 27 availability, 27 disease characteristics 15,27 and hobbies/interests 25 …”
Section: Discussionmentioning
confidence: 99%
“…Few peer support trials in T2D have factored in person‐centred qualities in the matching process. Moreover, the ‘match‐maker’ role has been assumed, primarily, by the research team rather than the participants themselves 15,24,26,27 . In this era of person‐centred and collaborative care, the power of decision‐making should be placed in the hands of participants as they know best what their own support needs, preferences, and priorities are.…”
Section: Discussionmentioning
confidence: 99%